Pendampingan Pembuatan Laporan Keuangan Bagi Pengrajin Tas Di Kecamatan Kasemen Kota Serang - Utami, Kurnia Dwi Sari; Fatoni, Ahmad (Penerbit Widina, Widina Media Utama, 2025)
The background to this service is the still low level of good financial management skills and adequate understanding of accounting. This community service program aims to assist bag craftsmen in Kasemen District, Serang City, in preparing financial reports to gain access to capital from financial institutions. Micro, small, and medium enterprises (MSMEs) often face obstacles in managing their finances, making it difficult for them to obtain the capital needed for business development. This assistance includes training on the main components of financial reports, namely the profit and loss statement, balance sheet, and cash flow, as well as a simulation of capital applications. The community service implementation method is carried out in 3 (three) stages: the preparation stage, the implementation stage, and the evaluation stage. The results of this activity show that with a better understanding of financial management, business actors can prepare neat financial reports and increase their opportunities in obtaining access to financing from financial institutions.ABSTRAKLatar belakang pengabdian ini adalah masih rendahnya kemampuan pengelolaan keuangan yang baik dan pemahaman akuntansi yang memadai. Program pengabdian ini bertujuan untuk mendampingi para pengrajin tas di Kecamatan Kasemen, Kota Serang dalam penyusunan laporan keuangan guna memperoleh akses permodalan dari lembaga keuangan. Pelaku usaha mikro kecil dan menengah (UMKM) sering menghadapi kendala dalam mengelola keuangan, sehingga menyulitkan mereka untuk mendapatkan modal yang diperlukan guna pengembangan usaha. Pendampingan ini mencakup pelatihan tentang komponen utama laporan keuangan, yaitu laporan laba rugi, neraca, dan arus kas, serta simulasi pengajuan permodalan. Metode pelaksanaan pengabdian yakni dengan 3 (tiga) tahapan yakni tahap persiapan, tahap pelaksanaan dan tahap evaluasi. Hasil dari kegiatan ini menunjukkan bahwa dengan adanya pemahaman yang lebih baik mengenai manajemen keuangan, para pelaku usaha mampu menyusun laporan keuangan yang rapi dan meningkatkan peluang mereka dalam mendapatkan akses pembiayaan dari lembaga keuangan.